2021
DOI: 10.1080/08897077.2021.1903653
|View full text |Cite
|
Sign up to set email alerts
|

Integrating DATA 2000 Waiver Training into Undergraduate Medical Education: The Time is Now

Abstract: Background Medications for opioid use disorder (MOUD) significantly reduce morbidity and mortality from opioid use disorder (OUD). To prescribe MOUD, physicians must obtain a DEA waiver through requirements outlined in the Drug Addiction Treatment Act of 2000 (DATA 2000). We developed an Addiction Medicine curriculum that features DATA 2000 waiver training at the Robert Larner, MD College of Medicine (LCOM). Methods All third-year medical students completed a virtual DATA 2000 waiver training at the commenceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Outside of this curriculum, the Quality Program has supported DOM faculty in developing and evaluating curricula to educate medical students and resident physicians about opioid prescribing and managing opioid use disorder. 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
“…Outside of this curriculum, the Quality Program has supported DOM faculty in developing and evaluating curricula to educate medical students and resident physicians about opioid prescribing and managing opioid use disorder. 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
“…Initiatives implementing the DATA wavier training with 3rd year medical students curricula shows similar positive results. For example, Riser and colleagues found statistically significant increases in knowledge of MOUD pharmacology, MOUD prescribing practices, and most students reported that the waiver training was relevant to their future practice [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…College of Medicine (LCOM) at the University of Vermont, 75% of third-year clerkship students who were required to complete virtual synchronous DATA training agreed or strongly agreed that they planned to provide MOUD as part of future practice before DATA training and 78% agreed or strongly agreed after DATA training—suggesting that the majority of current UME trainees may exhibit willingness to provide evidence-based therapies for OUD both at baseline and after dedicated teaching. 29 Indeed, LCOM students demonstrated significantly increased knowledge on MOUD pharmacology and best prescribing practices at post-test assessment. 29 Similarly, Wayne State University School of Medicine found that the incentive of additional study time motivated all 300 clerkship students to complete the virtual, self-paced 8-hour training provided through Providers Clinical Support System and the post-test assessment demonstrated that students had significantly improved their knowledge about the opioid epidemic and MOUD, as well as significantly increased their future intent to prescribe MOUD.…”
Section: Incorporating Moud Into Curriculamentioning
confidence: 95%
“…26–29 Indeed, all medical graduates from the Rutgers New Jersey Medical School or the Warren Alpert Medical School of Brown University or those who complete the free training provided jointly through the U.S. Substance Abuse and Mental Health Services Administration and the Providers Clinical Support System, beginning in 2020, can apply to become DATA waivered upon obtaining Drug Enforcement Administration licensure after graduation. 27–29…”
Section: Incorporating Moud Into Curriculamentioning
confidence: 99%
See 1 more Smart Citation